NORTH CAUCASIAN FEDERAL DISTRICT NEEDS UNIFIED LAW ON THE HIGHLAND AREAS - G. M. Abdurakhmanov; L. A. Dudurkhanova; R. Kh. Gayrabekova (Юг России: экология, развитие, 2015)
RETRACTED ARTICLEWe proposed a draft law on highland areas, which aims to create ecological and socio-economic legal framework for the sustainable development of highland areas of the North Caucasian Federal District, the conservation and sustainable use of natural resources, historical, cultural and architectural heritage.Conclusion. The adoption of this law will create a framework for the regulation of human activities and will maintain and reproduce the natural resources and cultural heritage in the highland areas of the North Caucasian Federal District, which will ensure the transition to sustainable development.